2014
DOI: 10.4103/1463-1741.132080
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus among Serbian secondary school students in relation to their behavior and habits

Abstract: Although tinnitus is a very common symptom, risk factors related to behavior and habits have not been sufficiently investigated. As no investigation on this problem has been performed in Serbia, the aim of our study was to establish the prevalence of tinnitus among Serbian adolescents and to investigate the relationship between their behavior and habits and tinnitus. This investigation was designed as a cross-sectional interview study among secondary school students in Belgrade, Serbia (277 boys and 494 girls)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…In this study, a large proportion of the adolescent patients with tinnitus had a history of bullying or isolation and of carrying a weapon (e.g., knife or club). In addition, the adolescent patients with tinnitus have a high prevalence of smoking, alcohol drinking, and substance abuse; [5,18,19,44] this is in agreement with our findings. Adolescent are vulnerable to substance abuse, which is common in those with psychiatric comorbidities.…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, a large proportion of the adolescent patients with tinnitus had a history of bullying or isolation and of carrying a weapon (e.g., knife or club). In addition, the adolescent patients with tinnitus have a high prevalence of smoking, alcohol drinking, and substance abuse; [5,18,19,44] this is in agreement with our findings. Adolescent are vulnerable to substance abuse, which is common in those with psychiatric comorbidities.…”
Section: Plos Onesupporting
confidence: 92%
“…This was the first official nationwide hearing survey of adolescents in South Korea. Previous studies used the data of the Korea National Health and Nutrition Examination Survey [ 15 18 ] or were questionnaire-based [ 8 , 19 ]. The National Health and Nutrition Examination Surveys of Korea and the United States collect comprehensive health data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rheumatoid arthritis, asthma, depression, thyroid disease, an abnormal tympanic membrane, and increased noise exposure (3,(15)(16)(17)(18). Hyperinsulinemia (17,19), drug abuse in boys and exposure to second hand smoke in girls (20), obesity, and diabetes mellitus (17), have also been identified as risk factors of tinnitus. However, the role of the sex difference on tinnitus loudness and annoyance is still inconclusive (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of their study showed that greater musical experience was positively linked to higher hearing thresholds. Marmut et al [7] reported that chances of tinnitus were 13 times higher among drug addicts compared with non-drug users. From the previous literature it can be concluded that modern lifestyle habits among youngsters are risk factors for hearing loss [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%